Protection status as determinant of carbon stock drivers in Cerrado sensu stricto. (25th May 2020) - Pereira, Kelly Marianne Guimarães; Cordeiro, Natielle Gomes; Terra, Marcela de Castro Nunes Santos; Pyles, Marcela Venelli; Cabacinha, Christian Dias; de Mello, José Márcio; van den Berg, Eduardo
Abstract: Aims: Natural vegetation plays an important role in global carbon cycling and storage. Thus, the Cerrado (Brazilian savannah) is considered a carbon sink because of its intrinsic characteristics. Our aim was to evaluate how the aboveground biomass and biodiversity relationship change between three Cerrado remnants with different protection status: a 'control area' (Legal Reserve area), a protected area (PA) and a non-protected area (Non-PA). Methods: All three studied fragments are situated in northern Minas Gerais state, Brazil. We estimated the aboveground carbon stocks based on the forest inventory. We also measured three dimensions of biodiversity metrics for each plot: functional trait dominance, taxonomic diversity and functional diversity. The following functional traits were evaluated for the species: wood density, maximum diameter and seed size. We carried out generalized linear models seeking to evaluate how carbon stocks, community-weighted mean (CWM) trait values, species richness and diversity, and functional diversity indices differ among the remnants. Important Findings: The Cerrado areas without protection status had lower carbon stocks, species richness, species diversity, functional richness and functional dispersion, whereas both PA and Non-PA had lower CWM maximum diameter and seed size compared with the Legal Reserve control area. Generalized linear models showed that carbon stocks, species and functional richness metrics were correlated within and across sites, and thus, species richness could serve as a good proxy for functional richness and carbon stocks. The carbon stocks were positively driven by species richness and CWM maximum diameter, while they were negatively driven by functional dispersion. Functional richness, species diversity and CWM seed size appeared in the set of best models, but with no significant direct effect on carbon stocks. Thus, we concluded that absence of protection in the Cerrado areas decreases both species richness and carbon stocks.